AB0924 Charcot Arthropathy: A Diagnostic Challenge in Diabetic Patients. Clinical Features of 21 Cases. (10th June 2014) - Casado, E.; Arévalo, M.; Giménez, O.; Orellana, C.; Graell, E.; Galisteo, C.; Larrosa, M.
Abstract : Background: Charcot arthropathy is a destructive arthropathy with severe bone resorption that occurs in patients with sensory neuropathy of any etiology. This arthropathy can be a diagnostic challenge, because it has little clinical expression and requires to be suspected by specialists not used to assess patients with joint pathology. Objectives: To analyze the clinical features of patients with Charcot arthropathy diagnosed in our department in the last years. Methods: We systematically reviewed cases with Charcot arthropathy diagnosed in our department in the last 12 years (2002-2013). Demographics, underlying disease, time since onset of the arthropathy, clinical characteristics and referral department were collected. Results: 21 cases of Charcot arthropathy (57% male), age 55.8 years (29-78) were confirmed. The underlying disease was 15 diabetes, 2 syringomyelia, 2 leprosy 1 Charcot-Marie-Tooth, and 1 idiopathic sensory autonomic polyneuropathy. Patients with diabetes had a disease of 13.5 years of evolution (range 1-25). Of these patients 73% had peripheral vascular disease and 93% almost had one cardiovascular risk factor. The patients came mainly from Endocrinology (34%). Other referral departments were: Emergency (16%), Vascular Surgery (14%), Podiatry (14%), Internal Medicine (9%), Neurology (5%) and Orthopaedics (5%). We observed a delayed diagnosis of the arthropathy, with a mean of 360 days (4-1500). The most common form of clinical presentation was: swelling (57%), mild pain (52%), deformity (38%), fracture (1 patient). In 1 patient the diagnosis was casual (radiological finding). Most patients (57%) had a trigger: local infection (58%), surgery (25%) or injury (17%). The most common site in patients with diabetes was the tarsus (87%). Conclusions: Charcot arthropathy is mostly seen in patients with long-standing diabetes with peripheral vascular disease associated with other cardiovascular risk factors. Patients come mostly from Endocrinology, and although half of the patients had a trigger there is a clear diagnostic delay. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4001